Photodynamic inactivation of a multispecies biofilm using curcumin and LED light - Quishida, Cristiane Campos Costa [UNESP]; De Oliveira Mima, Ewerton Garcia [UNESP]; Jorge, Janaina Habib [UNESP]; Vergani, Carlos Eduardo [UNESP]; Bagnato, Vanderlei Salvador; Pavarina, Ana Cláudia [UNESP] (Springer Nature, 2016)
This study evaluated the potential of curcumin-mediated antimicrobial photodynamic inactivation (API) on multispecies biofilms of Candida albicans, Candida glabrata, and Streptococcus mutans of different ages. Acrylic samples (n = 480) were made with standardized rough surfaces and incubated with bacteria and yeast for 24 or 48 h. API was performed with curcumin (80, 100, 120 μM) and LED light. Additional acrylic samples were treated with curcumin or LED light only. Positive control samples received neither light nor curcumin. After API, colony counts were quantified (CFU/mL), cell metabolism was determined by means of XTT assay, and the total biofilm biomass was evaluated using Crystal Violet (CV) staining assay and images were obtained by confocal laser scanning microscopy (CLSM). The data were analyzed by nonparametric two-way ANOVA and post hoc Tukey tests (α < 0.05). For 24-h biofilm, API resulted in statistically significant difference (ρ < 0.001) of viability of C. albicans compared with control (P−L−) for all Cur concentrations. For 48-h biofilm, API resulted in statistically significant difference (ρ < 0.001) compared with control only when Cur at 120 μM was used. API promoted statistically significant difference (ρ ≤ 0.001) in the viability of S. mutans and C. glabrata for all Cur concentrations in the two biofilm ages. In addition, API produced a statistically significant difference (ρ < 0.001) of metabolic activity and of total biomass (ρ < 0.001) of multispecies biofilms compared with control for all Cur concentrations. It can be concluded that both 24- and 48-h biofilms were susceptible to API mediated by Cur; however, 24-h biofilm was more sensitive than the 48-h biofilm.
Keywords: Bacteria; Fungi; Multispecies biofilm; Photodynamic inactivation